Monitoring the agri-food system in Myanmar: Rice millers – September 2024 survey round - Myanmar Agrifood Program for Strategy and Analysis (International Food Policy Research Institute, 2024)
In September 2024, we surveyed 256 rice millers from 12 states and regions across Myanmar to assess the impacts of the monsoon floods and the political crisis and related disruptions. This report presents the key results and analysis from those interviews.